Software defined wireless sensor networks application opportunities for efficient network management: A survey. (February 2018) - Modieginyane, Kgotlaetsile Mathews; Letswamotse, Babedi Betty; Malekian, Reza; Abu-Mahfouz, Adnan M.
Abstract: Wireless Sensor Networks (WSNs) are commonly used information technologies of modern networking and computing platforms. Today's network computing applications are faced with a high demand of powerful network functionalities. Functional network reach is central to customer satisfaction such as in mobile networks and cloud computing environments. However, efficient management of WSNs remains a challenge, due to problems supplemental to them. Recent technology shift proposes Software Defined Networking (SDN) for improving computing networks. This review paper highlights application challenges faced by WSNs for monitored environments and those faced by the proposed approaches, as well as opportunities that can be realized on applications of WSNs using SDN. We also highlight Implementation considerations by focusing on critical aspects that should not be disregarded when attempting to improve network functionalities. We then propose a strategy for Software Defined Wireless Sensor Network (SDWSN) as an effort for application improvement in monitored environments. Graphical abstracts: The following figure is the graphical abstract of the review paper.